The Realistic Worries and Reconstruction Path of Integrating Leisure Education into Curriculum from the Perspective of Dewey’s Curriculum Theory - Zhang, Dongnian (Transactions on Social Science, Education and Humanities Research, 2024)
In today’s rapidly developing economy, the transition from a working society to a leisure society has made the importance of leisure education increasingly prominent. However, due to the narrow educational concept, leisure education has not received the attention it deserves, making it difficult to realize its true educational value. As a life oriented educational activity, leisure education urgently needs to be integrated into school curriculum. From the perspective of Dewey’s curriculum theory, this paper explores the direction of curriculum in contemporary leisure education, examines the reflection of real-life concerns such as "cognitive degradation", "temporal and spatial alienation", and "the disappearance of contemplation" in the era, and explores the reconstruction path of integrating leisure education into curriculum based on the theory of activity curriculum.